Experimentation of classic digital controllers in an embedded system applied in a thermal process (2018)
This research project shows the implementation of classic digital controllers in an embedded system to control the temperature of a thermal system. The embedded system selected was in the computer board Raspberry Pi 2 B+ together with an ONE Arduino board. In the measurement stage the hardware was developed for to transmit the temperature data from the PT-100 thermometer resistance towards the Raspberry PI. For the implementation of the computational stage was developed an algorithm for the different controllers and based on this the controllers were programmed in Python 2.7. For the actuator a power stage was designed that converts the ac voltage into a voltage dc, from a PWM signal. This dc voltage is used to feed a thermal resistance that is responsible for executing the control action of the system. With the implementation of the types of controllers, a comparative analysis was realized highlighting the most relevant characteristics for each type of controller and allowing to also evaluate the performance of the Raspberry Pi. Based on the results obtained in the execution of the project, it concluded the feasibility to control thermal systems under different types of controllers embedded in the Raspberry Pi and with the possibility of developing intelligent control strategies for futures projects, through the use of software tools and free hardware.